TINAG mutation as a genetic cause of pectus excavatum. (April 2020) - Tong, Xing; Li, Guangbin; Feng, Yu
Abstract: To investigate the possible involvement of germline mutations in pectus excavatum (PE). We investigated a four-generation pedigree with PE. Whole-exome sequencing (WES) was performed to identify potential mutations for PE formation. Sanger sequencing was used to validate these mutations. hFOB1.19 cell proliferation was measured with a Celigo imaging cytometry system. There were four PE patients in this four-generation pedigree. In the four patients, we identified a novel heterozygous stop-gain variant in Tubulointerstitial Nephritis Antigen (TINAG) through exome sequencing: c.G2A, p.W2*. This mutation was validated by Sanger sequencing. Knockdown of TINAG inhibited the proliferation of hFOB1.19 cells. Based on these results, we hypothesize that the TINAG c.G2A mutation is a loss-of-function mutation that reduces TINAG expression. Increasing TINAG warrants further investigation as a potential novel anabolic mechanism of PE treatment.